The discursive positioning of students with special educational needs in four UK primary classrooms - Efthymiou, Efthymia (2013)
The debate about inclusion of children with special educational needs (SEN) in mainstream education in the UK partly revolves around what makes the classroom environment inclusive. Social and local conceptualisations of government guidelines, as well as specific school agendas, currently influence a range of practices. This study aims to identify ways in which multimodal discourses and particular pedagogic approaches shape the positioning and identification of students with SEN in four primary school classrooms. It investigates whether the practical discursive positioning of students with SEN in these four classrooms can deliver inclusion. The study considers the views and behaviour of primary school students with and without SEN, primary school teachers and teaching assistants (TAs) in one Steiner and two mainstream schools. Drawing on a multimodal approach to discourse analysis which aims to account for the complex relationships between symbolic and non- verbal modes of classroom signification, the study explores ways in which meaning is produced in classrooms and the ways in which children's modes of communication, as well as teachers' practices, are discursively constructed. Four classrooms are compared on the basis of teaching observations, interviews, transcription of dialogues, and analysis of classroom organisation and decoration. It appears that the mainstream primary classrooms, which are characterised by stronger classification and framing and greater degrees of teacher-centred pedagogic discourse, establish strict boundaries around knowledge construction which influence the access to understanding and social positioning of students with SEN. Within these mainstream classrooms, there are barriers to full social and academic inclusion. By contrast, in the Steiner classroom, the inclusion of students with SEN is more effective, due to weaker boundaries around the content of constructed knowledge, more student-centred approaches and a higher degree of symmetrical interaction between teacher and students who actively participate in the production of knowledge. Based on this limited sample, it is suggested that the diverse needs of SEN students do not tend to be supported effectively by the practices of mainstream schools. A shift to more student-centred approaches is necessary.